Free Radical-scavenging Activity and Anthocyanin Profiles of Cabernet Sauvignon and Merlot Wines from Four Wine Grapegrowing Regions in China - Jiang, B.; Zhang, Z-W (South African Journal of Enology and Viticulture, 2018)
The present study focused on the free radical-scavenging activity and anthocyanin profiles of Cabernet Sauvignon and Merlot wines produced from four different regions in China. The anthocyanin profiles in all wine samples were analysed by HPLC-MS/MS, while the free radical-scavenging activity was estimated by the DPPH assay. The results show that the contents of phenolic subclasses and the levels of antioxidant activity in all wine samples varied greatly among cultivars and environmental factors of vine growth, and these values were the most prominent in Yuquanling regional wines. As the main components in anthocyanins, the percentages of malvidin-3-O-glucoside and its derivatives showed differences within grape cultivars in the different regional wines; these monomeric anthocyanins (not present simultaneously in the four regional wines studied within grape cultivars) had concentrations below 10 mg Mv/L. The significant correlation was obtained between DPPH-scavenging ability and the total phenolic, flavonoid and anthocyanin content. It can be concluded that this information could be used as a biochemical marker for the authenticity of the single-cultivar red wines that were produced from the four regions above.